Against the grain: Teaching Transgender Human Rights. (June 2013) - Irving, Dan
Mirroring the course objectives of my senior undergraduate Transgender Human Rights seminar, this article seeks to challenge trans rights politics. Many rights advocates emphasize the symbolic value of formal acknowledgment of, and protection for, gender identity. I argue that trans rights are achieved through the production of deserving subjects according to colonial, heteronormative, nationalist and capitalist logics. Rights discourses are injurious to a significant number of trans and two-spirit individuals and communities because they obscure relations of governance. Rights ought not to be the driving force of 'trans-' efforts to cultivate broader relations of political solidarity to challenge interlocking systems of power.